Moodle and nursing teaching - a brief experience report - Isabel CF da Cruz (Universidade Federal Fluminense, Escola de Enfermagem Aurora de Afonso Costa, 2009)
Distance-learning based on the web am Technology Information (TI) have  been important in recent health policy initiatives, but still a challenge for nursing. This article points out an experience with Moodle to support Nurse Education.